The Effect of Combined (physical skill) Exercises on Some Physical Abilities That Affect the Technical Skills Accuracy In Squash Game - Qaddouri, Yaser Wajih; Salman, Mohammed Ghazi (International Journal of Psychosocial Rehabilitation, 2020)
The player’s achievement to access to higher levels requires concerted efforts, a proper diagnosis of strengths and weaknesses, and work to develop what serves the effectiveness or skill. The research problem lies in a difference in the physical effort performed by the players in every match and this is shown by repeating skill errors through late reach to the ball is a result of the effort exerted in the match. This difference appears in the last half of the match and the accompanying decrease in the physical and functional effort of the players, especially since the squash player needs to invest all physical abilities and employ them with skillful performance, as squash is one of the games that need physical and skillful abilities high throughout the interchange of playing balls until an opportunity is obtained to implement a skill precisely in a place far from the presence of the opposing player and win the match.